Malaria in Pregnancy - Musa, Juna; Saadi, Samer; Guy, Ali; Madani, Kulsum; Abdullahu, Blina; Barakat, Benan; Kola, Ina; Zylalaj, Ilda; Elrefaei, Amro; Musa, Dorina (Archives of Clinical and Medical Case Reports, 2020)
Malaria is a potentially life-threatening disease that is transmitted by the bite of an infected Anopheles mosquito. Five known species of genus Plasmodium infect humans: Plasmodium vivax, Plasmodium ovale, Plasmodium Knowlesi, Plasmodium Malariae and Plasmodium falciparum. Malaria infection during pregnancy is a significant public health problem with substantial risks for the pregnant woman, her fetus and the newborn child.. The symptoms and complications vary according to malaria transmission intensity in the given area and the individual’s level of acquired immunity. Presented below is a case of a 26-years old primigravida, who returned to the UK from Nigeria after one week presenting with a 24 hour history of abdominal pain, nausea, vomiting and signs of sepsis. During her hospitalization, despite being treated for sepsis, the patient’s overall condition did not improve, therefore suspicion for malaria became very questionable. In consideration of the patient’s history and clinical presentation; a thorough investigation was to take in effect for this possible infection. Once diagnosis of malaria was confirmed, the appropriate treatment was administered.